Factors Related with Unsafe Action in Palm Oil Harvesters at PT. Priatama Riau Kebun Rupat Island - Iskandar Iskandar; Y. Denny A. Wahyudiono; Noeroel Widajati; Zulkifli Zulkifli (Universitas Airlangga, 2023)
Introduction: Work accidents can be caused by unsafe action factors in the field, such as not wearing personal protective equipment (PPE), not following work procedures, and not following work safety regulations. The purpose of this study was to analyze the factors related to unsafe actions (unsafe behavior) in oil palm harvesters at PT Priatama Riau. Methods: This is an observational study. The study population consisted of 111 workers in the plantation harvester section. The research sample was calculated using the Slovin formula for as many as 86 workers. The independent variables consisted of OHS knowledge, attitudes, education, length of working period, age, OHS supervision, and OSH training. The dependent variable was Unsafe Action (unsafe behavior). Essential information was obtained through meetings, perceptions, and polls. The information collection instruments used in this study were survey sheets, agenda sheets, and cameras for documentation. Data analysis consisted of univariate and bivariate analyses. Bivariate analysis was performed using the chi-squared statistical test. Results: The factors related to unsafe action/unsafe behavior in oil palm harvesters were sex, years of service, knowledge, attitudes, OHS supervision, OHS training, and unsafe conditions. Conclusion: Judging from the factual test as a whole or together, the factors of tenure, gender, attitude, knowledge, OSH supervision, OSH training, work equipment, and unsafe conditions are related to Unsafe Actions.